Efeito inibidor de leucotrieno (MK 0476) em modelo experimental da Síndromedo Desconforto Respiratório Agudo (SDRA) induzida por Lipopolissacarídeo (LPS) - Chiovatto, Jaime Eduardo Davino (2015)
The acute respiratory distress syndrome (ARDS) has high mortality rates and may be the result both of lung infections such as extra pulmonary being characterized by respiratory failure from the inflammatory response that leads to alteration of alveolar-capillary permeability, edema and hypoxemia refractory to high flows oxygen. One of the most important mechanisms that determine the severity of this injury is the magnitude of the alveolar epithelial barrier injury. The possibility of epithelial repair at an early stage is the major determinant of recovery. Many of the therapeutic approaches in attempts to permeate decreased pulmonary inflammation to minimize the initial injury, which is largely due to the inflammatory process mediated by local and systemic activation by cytokines such as TNF-α and IL-8. In this sense, we aimed to evaluate the effects of leukotriene inhibitor (MK0476) on pulmonary and systemic inflammation. For this purpose, C57BL / 6 mice (n = 35) adults male were distributed into five groups: (1) Control 24 hours (n = 7; unhandled), (2) Control 48 hours (n = 7; unhandled) (3) Control IT LPS 24 hours (n = 7; intratracheal LPS; 10 mg / mouse) (4) Control IT LPS 48 hours (n = 7; intratracheal LPS; 10 mg / mouse), (5) IT + LPS MK0476 (n = 7; intratracheal LPS; 10mg / mouse + MK0476) .The animals were euthanized twenty-four hours after the LPS administration and evaluated the total cell and differential count in broncho alveolar lavage (BAL) protein levels in total BAL cytokine levels (IL-6, CXCL-1 / KC, IL-10, IL-17 and TNF-α) in serum and BAL supernatant and the density of neutrophils, lymphocytes and macrophages in the lung parenchyma. They also assessed the levels of VEGF in lung homogenate, and the expression of NF-kB and LTB4R leukocytes in the pulmonary parenchyma through imunohistochemistry. Moreover, IL-8 levels in the supernatant of human neutrophils stimulated in vitro with LPS (1.5 ug / ml of medium) and treated with MK0476 (10uM) was also evaluated. The results showed that the MK0476 is capable of decreasing the number of total cells (p <0.05), macrophages (p <0.05), neutrophils (p <0.01) and lymphocytes (p <0.001) in BAL, in addition to total protein levels (p <0.05), IL-6 (p <0.05) CXCL1 / KC (P <0.05), IL-17 (p <0.05) and TNF-α (p <0.05). The density of neutrophils (p <0.001), lymphocytes (p <0.001) and macrophage (p <0.01) in the lung parenchyma was also reduced by treatment with the MK0476. VEGF levels in lung homogenate (p <0.01) were re-established by treatment with the MK0476. Finally, treatment with the MK0476 is capable of reducing the expression of NF-kB and LTB4R leukocytes in the pulmonary parenchyma, suggesting a possible mechanism of action of MK0476 in acute lung inflammation induced by LPS. We therefore conclude that the MK0476, the model used, presents significant improvement in the levels of total proteins and cytokines, improving both systemic levels and local.